Utilisation of maternity waiting homes and its associated factors in Ethiopia: Systematic reviews and meta-analysis - Bekalu Getnet Kassa; Alemu Degu Ayele; Habtamu Gebrehana Belay; Gedefaye Nibret Mihiretie; Mulugeta Dile Worke (Elsevier, 2021)
Background: Maternity waiting homes are residential facilities near or in a qualified medical facility where women classified as "high risk" can wait for their delivery before being transferred to a nearby medical facility. Ethiopia has been implementing maternity waiting homes to reduce maternal and prenatal mortality, though utilisation varies significantly between facilities. Thus, this systematic review and meta-analysis was aimed to estimate the pooled prevalence and determinants of maternity-waiting home utilisation in Ethiopia. Methods: In this study, variables were searched from different electronic database systems, including PubMed/Medline, CINHAL, Scopus, Web of sciences, google scholar and Grey literature. Data were extracted guided by a standardised data collection measurement tool. The data were analysed using STATA 16 statistical software, and I2 tests assessed heterogeneity between the studies. A random-effect model was used to forecast the pooled utilisation of maternity waiting homes. Results: Twelve observational studies were included in this review. The pooled prevalence of utilisation of maternity waiting homes in Ethiopia was 44.91%. Attended antenatal care visits (OR = 2.87, 95%CI, 1.75-4.69), history of complication (OR = 2.05, 95%CI, 1.32-3.16), travel time to obstetric care facility >30 min (OR = 2.75, 95%CI, 1.87-4.06), poverty (OR = 4.04, 95%CI, 1.46-11.19), experience of maternity waiting home use (OR = 2.90, 95%CI, 1.14-7.38) and childbirth in the health facility (OR = 11.86, 95%CI, 4.02-35.01) were significantly associated with utilisation of maternity waiting home. Conclusions: This systematic review and meta-analysis revealed that the utilisation of maternity-waiting homes was low in Ethiopia. Thus, concerned stakeholders must design and implement effective interventions to increase maternity-waiting home utilisation and tackle the determinants that deter its utilisation.